The Role of the NLRP3 Inflammasome in Mediating Glomerular and Tubular Injury in Diabetic Nephropathy - Williams, B. M.; Cliff, C. L.; Lee, K.; Squires, P. E.; Hills, C. E. (Frontiers in Physiology, 2022)
The NOD-like receptor protein 3 (NLRP3) inflammasome is a multi-protein signalling complex integral to the chronic inflammatory response, activated in response to sterile and non-sterile cellular damage. The assembly and activation of the NLRP3 inflammasome comprise a two-step process involving nuclear factor kappa B (NFkB)-mediated priming, followed by canonical, non-canonical or alternative signalling pathways. These result in the maturation and release of inflammatory cytokines interleukin-1beta (IL1ß) and interleukin-18 (IL18), which are associated with chronic inflammatory conditions including diabetic kidney disease. Diabetic nephropathy is a condition affecting ~40% of people with diabetes, the key underlying pathology of which is tubulointerstitial inflammation and fibrosis. There is growing evidence to suggest the involvement of the NLRP3 inflammasome in this chronic inflammation. Early deterioration of kidney function begins in the glomerulus, with tubular inflammation dictating the progression of late-stage disease. Priming and activation of the NLRP3 inflammasome have been linked to several clinical markers of nephropathy including proteinuria and albuminuria, in addition to phenotypic changes including mesangial expansion. Treatment options for diabetic nephropathy are limited, and research that examines the impact of directly targeting the NLRP3 inflammasome, or associated downstream components are beginning to gain favour, with several agents currently in clinical trials. This review will explore a role for NLRP3 inflammasome activation and signalling in mediating inflammation in diabetic nephropathy, specifically in the glomerulus and proximal tubule, before briefly describing the current position of therapeutic research in this field.